Comparing the corrosivity of acidic species in petroleum fractions by raman spectroscopy, energy-dispersive spectrum and scanning electron microscopy. (2nd November 2017) - Lu, Ya; Jia, Lingyan
ABSTRACT: The main object of this work was to compare the corrosion powers of acidic species: naphthenic acid, fatty acid and aromatic acid which were found in petroleum fraction. They were blended into base oils to formulate three simulate oils (E, F and G) with the same TAN values of 2.3 mg KOH/g. AISI 316 steel surfaces immersed in oils were measured by Raman spectroscopy, energydispersive spectrum and scanning electron microscopy after 24, 48, 72 h to evaluate their corrosion. From the Raman images, the corrosion products were confirmed. Besides goethite (α-Fe(OOH)) in corrosion product E at 48 hours; magnetite (Fe3 O4 ) in F at 24 hours; and hematite (α-Fe2 O3 and α-Fe2 O3 ) in G at 72hours, there were disordered carbons on steel E and ferric benzoate film on steel G. The contents of elements from EDS have markedly different characteristics, indicating that dominant corrosion products on steel samples resulted from three acidic species are different. The morphology in SEM also corroborated above data that corrosion products have difference. Combining the data of three measurements, the rank of corrosion power based on the formations of ferric oxides was determined: fatty acid > naphthenic acid > aromatic acid.